Interexaminer reliability of the assessment of clinical furcation parameters as related to different probes - Eickholz, Peter; Steinbrenner, Harald; Lenhard, Markus; Marquardt, Moritz; Holle, Rolf (European journal of oral sciences, 1999)
The aim of this study was to investigate the interexaminer reliability of the assessment of clinical furcation diagnosis. Horizontal attachment level (PAL-H) measurements were obtained by 3 examiners in 6 molars in each of 10 patients with advanced periodontitis.